Deskripsi Penerapan Literasi Budaya Dan Kewargaan Dala Pembelajaran PPKn Di Kelas III SD Negeri 12 Pontianak Kota - Stepanus Roby; Asmayani Salimi; Rio Pranata (Journal on Education, 2023)
The research aims to identify and describe the planning and implementation of the application of cultural literacy and citizenship in civics learning in class III SD Negeri 12 Pontianak Kota. This study used descriptive qualitative method. The results of this study are that the planning for implementing cultural literacy and citizenship in Civics learning in grade III elementary schools has been almost completely planned and implemented. The implementation of the application of cultural literacy and citizenship in Civics learning in class III SD Negeri 12 Pontianak City is concluded that more than half of the aspects of cultural literacy and citizenship have been implemented, of the 7 aspects of cultural literacy and citizenship that the researchers obtained from interviews with teachers, a review RPP, and observations in class III it was found that 5 aspects of cultural literacy and citizenship had been implemented, and 2 other aspects had not been implemented in class III SD Negeri 12 Pontianak Kota.